Measuring taxes on income from capital - Michael P. Devereux (Institute for Fiscal Studies (IFS), 2003)
This paper reviews how the impact of taxes on the incentive to invest in the corporate sector can be measured. The main focus of the paper is to discuss measures derived from economic theory. In empirical work, these tend to be based on the legal parameters of tax regimes, rather than on observed tax revenues or tax liabilities. A basic model is set up which yields two measures, reflecting two alternative forms of investment decision. An effective marginal tax rate is relevant for decisions concerning the scale of the capital stock. An effective average tax rate is relevant for discrete investment choices.
Keywords: 330; Kapitalertragsteuer; Steuerbelastung; Steuerwirkung; Investition; Kapitalkosten; Theorie